Case Report: A Programmed Cell Death-1 Inhibitor-Related Abdominal Fibroinflammatory Reaction Affecting Multiple Organs in A Non-Small-Cell Lung Cancer Patient - Chen, An-Tian; Shi, Yue-Quan; Tan, Bei; Zhu, Liang; Luo, Ya-Ping; Zhong, Wei; Wang, Meng-Zhao; Xu, Yan (Frontiers in Immunology, 2022)
Immunotherapy utilizing programmed cell death-1 (PD-1)/PD-L1 inhibitors has been regarded as a rising hope for tumor patients, and their effects have been demonstrated in many clinical trials. However, immune-related adverse events also occur in patients and can sometimes have severe consequences. Pembrolizumab (Keytruda) is a humanized monoclonal anti-PD-1 antibody that has been approved by the US Food and Drug Administration for non-small-cell lung cancer. Here, we report a rare case of an abdominal fibroinflammatory reaction that affected multiple organs during anti-PD-1 immunotherapy using pembrolizumab in a non-small-cell lung cancer patient. The patient’s case demonstrates that immunotherapy-related abdominal fibroinflammatory reactions need to be considered, especially for patients with a history of pre-existing conditions in the abdomen. Glucocorticoids may be useful as a treatment when a diagnosis is confirmed.